Cavernous Malformations of the Optic Nerve and Optic Pathway: A Case Series and Systematic Review of the Literature. Issue 5 (30th August 2021) - Srinivasan, Visish M; Koester, Stefan W; Wang, Michele S; Rahmani, Redi; Ma, Kevin L; Catapano, Joshua S; Labib, Mohamed A; Lawton, Michael T
Abstract: BACKGROUND: Although rare, cavernous malformations (CMs) of the optic nerve and anterior optic pathway (optic pathway cavernous malformations [OPCMs]) can occur, as described in several single case reports in the literature. OBJECTIVE: To describe the technical aspects of microsurgical management of CMs of the optic pathway on the basis of an extensive single-center experience and review of the literature. METHODS: A systematic literature review was performed to augment an earlier review, using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. In addition, an institutional database was searched for all patients undergoing surgical resection of OPCMs. Patient information, surgical technique, and clinical and radiographic outcomes were assessed. RESULTS: Since the previous report, 14 CMs were resected at this institution or by the senior author at another institution. In addition, 34 cases were identified in the literature since the systematic review in 2015, including some earlier cases that were not discussed in the previous report. Most OPCMs were resected via pterional, orbital-pterional, and orbitozygomatic craniotomies. Visual outcomes were similar to those in earlier reports, with 70% of patients reporting stable to normal vision postoperatively. CONCLUSION: OPCMs can occur throughout the anterior visual pathway and may cause significant symptoms. Surgery is feasible and should be considered for OPCMs presenting to a surface of the nerve. Favorable results can be obtained with resection, although optimal results are obtained with patients who present with milder symptoms without longstanding damage to the optic apparatus.